High incidence of early anaphylactoid reaction to SAIMR polyvalent snake antivenom. - Moran, N; Newman, W; Theakston, R; Warrell, D; Wilkinson, D (1998)
During a prospective study of 147 patients with snakebite presenting to a rural South African hospital, 13 of 17 patients (76%) treated with South African Institute for Medical Research (SAIMR) polyvalent antivenom experienced potentially severe early (anaphylactoid) reactions. The most common reaction was generalized urticaria (12; 71%), but 3 cases of angio-oedema (18%), 2 of bronchospasm (12%), and 2 of hypotension (12%) were also observed. Reactions were controlled with adrenaline, antihistamines, and resuscitation. All patients fully recovered from envenoming although the full dose of antivenom was not given to most. Indications for the use of this antivenom should be reconsidered and patients should be given antivenom in a high care setting if possible. Use of antivenom by lay people outside hospital should be discouraged and antivenom manufacturing processes could usefully be reviewed.